Massive Magnetostriction of the Paramagnetic Insulator KEr(MoO4)2 via a Single‐Ion Effect. (10th December 2021) - Bernáth, Bence; Kutko, Khrystyna; Wiedmann, Steffen; Young, Olga; Engelkamp, Hans; Christianen, Peter C. M.; Poperezhai, Sergii; Pourovskii, Leonid V.; Khmelevskyi, Sergii; Kamenskyi, Dmytro
Abstract: The magnetostriction phenomenon, which exists in almost all magnetically ordered materials, is proved to have wide application potential in precision machinery, microdisplacement control, robotics, and other high‐tech fields. Understanding the microscopic mechanism behind the magnetostrictive properties of magnetically ordered compounds plays an essential role in realizing technological applications and helps the fundamental understanding of magnetism and superconductivity. In paramagnets, however, the magnetostriction is usually significantly smaller because of the magnetic disorder. Here, the observation of a remarkably strong magnetostrictive response of the insulator paramagnet KEr(MoO4 )2 is reported on. Using low‐temperature magnetization and dilatometry measurements, in combination with ab initio calculations, employing a quasi‐atomic treatment of many‐body effects, it is demonstrated that the magnetostriction anomaly in KEr(MoO4 )2 is driven by a single‐ion effect. This analysis reveals a strong coupling between the Er 3+ ions and the crystal lattice due to the peculiar behavior of the magnetic quadrupolar moments of Er 3+ ions in the applied field, shedding light on the microscopic mechanism behind the massive magnetostrictive response. Abstract : The paramagnetic single‐crystal insulator KEr(MoO4 )2 exhibits a remarkable change of its size in a magnetic field. This experimental feature exceeds the analogous effect in other paramagnets and rare‐earth alloys by an order of magnitude. The provided theoretical approach explains the mechanism behind this effect. The tunability of the crystal size provides excellent perspectives for applications in magnetic and cryogenic technologies.